2017
DOI: 10.1038/srep45176
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics may delay the progression of nonalcoholic fatty liver disease by restoring the gut microbiota structure and improving intestinal endotoxemia

Abstract: Gut-derived bacterial lipopolysaccharide (LPS) and subsequent hepatic toll-like receptor 4 (TLR4) activation have been recognized to be involved in the onset of diet-induced nonalcoholic fatty liver disease (NAFLD), but little is known about the variation of LPS and TLR4 during the progression of NAFLD. Probiotics were able to inhibit proliferation of harmful bacteria and improve gastrointestinal barrier function. However, it’s unclear whether LPS/TLR4 is involved in the protection effect of probiotics on NAFL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
165
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(191 citation statements)
references
References 52 publications
4
165
0
2
Order By: Relevance
“…Because oxidative stress and inflammation are the major risk factors involved in the pathogenesis of NAFLD, nut intake might have preventive effects on NAFLD through anti‐oxidant and anti‐inflammatory effects. Fourth, emerging evidence has shown that the dysbiosis of gut microbiota plays a critical role in pathogenesis of NAFLD . A recent review documented that non‐bioaccessible material from nuts can provide substrates for the human gut microbiota, thereby producing prebiotic properties …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because oxidative stress and inflammation are the major risk factors involved in the pathogenesis of NAFLD, nut intake might have preventive effects on NAFLD through anti‐oxidant and anti‐inflammatory effects. Fourth, emerging evidence has shown that the dysbiosis of gut microbiota plays a critical role in pathogenesis of NAFLD . A recent review documented that non‐bioaccessible material from nuts can provide substrates for the human gut microbiota, thereby producing prebiotic properties …”
Section: Discussionmentioning
confidence: 99%
“…Fourth, emerging evidence has shown that the dysbiosis of gut microbiota plays a critical role in pathogenesis of NAFLD. 37,38 A recent review documented that non-bioaccessible material from nuts can provide substrates for the human gut microbiota, thereby producing prebiotic properties. 39 The major strength of this study includes its large sample size, the use of a validated FFQ, and a robust statistical analysis with adjustment for established and potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Xue et al analysed the effects of combined probiotics on the LPS/TLR4 pathway . First, they showed in a rat model that serum LPS and liver TRL4 were highly increased during the progression of NAFLD.…”
Section: Methodsmentioning
confidence: 99%
“…The probiotic with combined bacteria (LGG, Lactobacillus plantarum WCFS1 and anthraquinone from cassia obtusifolia L.) also effectively reduced blood lipid levels and improved insulin resistance in NAFLD rats [96]. Meanwhile, supplementation of combined probiotic (Bifidobacterium infantis, Lactobacillus acidopilus and Bacillus cereus) could improve gut dysbiosis and liver function via suppression on LPS/TLR4 signaling pathway [97]. Kim DH et al found that consumption of kefir (a probiotic beverage containing over 50 species of lactic acid bacteria and yeast) prevented obesity and NAFLD formation by restoring gut microbiota and enhancing fatty acid oxidation in HFD-fed mice [98].…”
Section: Gut Microbiota-targeted Therapies Of Nafldmentioning
confidence: 99%
“…Improving NAFLD HFD-induced NAFLD in rats [96] Delaying the progression of NAFLD via LPS/TLR4 signaling HSHF diet-induced NAFLD in rats [97] Improving NAFLD pathogenesis and steatosis…”
Section: Probiotic Mixturesmentioning
confidence: 99%